Growth and physiological responses of four kiwifruit genotypes to salt stress and resistance evaluation - Yun-peng ZHONG; Xiu-juan QI; Jin-yong CHEN; Zhi LI; Dan-feng BAI; Cui-guo WEI; Jin-bao FANG (Journal of Integrative Agriculture, 2019)
In this study, four genotypes (Acva-1, Acva-2, Acva-3 and ZM-2) of Actinidia germplasm resources were grown in different NaCI concentrations (0, 0.4, 0.8 and 1.2 g L–1). The growth, physiological and biochemical indicators were measured, and a graded scale was developed as the salt damage index (SDI) according to different damage symptoms in leaves. The results showed SDI increased gradually, and average number and length of new shoot decreased significantly. Three antioxidant enzymes (superoxide dismutase, peroxidase and catalase) and two osmotic adjustment substances (soluble sugar and proline) showed different changes in old and new leaves of four genotypes. SPAD values exhibited a decreased trend in the whole except in the new leaves of Acva-2. Malonaldehyde contents increased and root activity decreased with the increasing salt concentrations. Principal component analysis was used to assess the salt tolerance, and the results showed Acva-3, from Actinidia valvata Dunn., had the strongest tolerance to salt, and could be a potential resistant resource to the salt-tolerance dedicated rootstock breeding of kiwifruit.